ANTARES and KM3NeT programs for the supernova neutrino detection. Issue Volume 12:Issue S331(2017) (17th October 2017) - Kulikovskiy, Vladimir
Abstract: The currently working ANTARES neutrino telescope has capabilities to detect neutrinos produced in astrophysical transient sources. Neutrino alerts are regularly generated to trigger multi-wavelength observatories. Potential sources include gamma-ray bursts, core-collapse supernovae, and flaring active galactic nuclei. In particular, the neutrino detection together with the multi-wavelength observations may reveal hidden jets in the supernova explosions. Supernovae remnants are currently the most promising acceleration sites of the cosmic rays in our Galaxy. The neutrino emission is expected during the cosmic ray interaction with the surrounding matter. The neutrino telescopes in the Northern hemisphere have excellent visibility to the most of the galactic supernovae remnants. Recent results on the search for point-sources with the ANTARES detector and the prospects for the future KM3NeT detector are presented. Although ANTARES and KM3NeT detectors are mainly designed for high energy neutrino detection, the MeV neutrino signal from the supernova can be identified as a simultaneous increase of the counting rate of the optical modules in the detector. The noise from the optical background due to 40 K decay in the sea water and the bioluminescence can be significantly reduced by using nanosecond coincidences between the nearby placed photomultipliers. This technique has been tested with the ANTARES storeys, each one consisting of three 10-inch photomultipliers, and it is further optimized for the KM3NeT telescope where the directional optical modules containing 31 3-inch photomultipliers provide very promising expectations.